Photoaffinity Ligand of Cystic Fibrosis Corrector VX-445 Identifies SCCPDH as an Off-Target - Minsoo Kim (171626) (2025)
Cystic fibrosis (CF) pharmacological correctors improve the cystic fibrosis transmembrane conductance regulator (CFTR) protein trafficking and function. Several side effects of these correctors and adverse drug interactions have been reported, emphasizing the need to understand off-targets. We synthesized VU439, a functionalized photoaffinity ligand (PAL) of VX-445. Chemoproteomics analysis by mass spectrometry (MS) was used to identify cross-linked proteins in CF bronchial epithelial cells expressing F508del CFTR. We identified saccharopine dehydrogenase-like oxidoreductase (SCCPDH), an uncharacterized putative oxidoreductase, as a VX-445-specific off-target. We also characterized changes in the metabolomic profiles of cells overexpressing SCCPDH to determine the consequence of binding of VX-445 to SCCPDH. These data show dysregulation of amino acid metabolism and a potential inhibitory activity of VX-445 on SCCPDH. The identified off-target may explain the exacerbation of psychological symptoms observed in the clinic, thus emphasizing the need for further optimization of correctors.